ANALISIS RELEVANSI MATERI JUAL BELI, KHIYAR, QIRAD, RIBA DALAM BAHAN AJAR MTS BERDASARKAN PERSPEKTIF TAKSONOMI BLOOM - Jannah, Miftakhul; Pratama, Farandika Nanda (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This research aims to analyze the content of class IX jurisprudence teaching materials for the 2013 curriculum published by the Indonesian Ministry of Religion in 2020, chapter II, buying and selling, khiyar, qirad and usury from the perspective of Bloom's taxonomy. This research uses a qualitative approach and library research methods with data analysis techniques, namely descriptive analysis. The results of his research show that this teaching material is relevant to the cognitive domain which covers five of the six levels in the cognitive domain, and covers all affective levels, as well as the psychomotor domain which is proven by learning lessons that can be emulated and used as role models for students. Likewise, the realm of psychological development is appropriate to the age of students at the MTs level who are entering the teenage years of student psychological development. Even though there are shortcomings from the perspective of Bloom's taxonomy, this teaching material has met the standards and has become a guide to the learning process, where researchers hope that the preparation of this teaching material can be further improved. Keywords: Analysis, Relevance, Fiqh Material, Teaching Material, Bloom's Taxonomy